Vegetation and Arthropod Responses to Brush Reduction by Grubbing and Stacking - Carter Crouch; J. Alfonso Ortega-Santos; David B. Wester; Fidel Hernández; Leonard A. Brennan; Greta L. Schuster (National Quail Symposium Proceedings, 2017)
Grubbing is a mechanical brush-reduction technique that allows targeting of mesquite (Prosopis glandulosa) and huisache (Vachellia farnesiana) and can be used to open lanes for hunting northern bobwhites (Colinus virginianus). Follow-up treatments of stacking allow the piling up of downed brush. We initiated this study on the Santa Gertrudis Division of the King Ranch, Inc., Texas, to determine effects of grubbing and stacking on vegetation and arthropod communities important to bobwhite. We hypothesized that grubbing and stacking would be able to selectively remove mesquite and huisache while leaving mixed brush species largely intact. We hypothesized that soil disturbance treatments would lead to improved brooding, feeding, and nesting habitat for bobwhite through an increase in herbaceous food plants, arthropods, and nesting cover. We sampled vegetation prior to treatment during July 2012 and posttreatment during November 2012, March 2013, and July 2013. We sampled arthropods before treatment in July 2012 and monthly posttreatment until July 2013, a year marked by extreme drought in South Texas. We detected a positive response of bobwhite food grasses and/or sedges 1 year after initial treatments but detected no treatment effect on bobwhite food forbs. We detected no effects of treatments on nesting cover. Grubbing and stacking did not affect total Insecta abundance; however, Insecta biomass and Arachnida abundance and biomass responded both positively and negatively to treatments. To better understand the effects of grubbing and stacking, replication of this study during years of average and above average precipitation should be conducted.
Keywords: northern bobwhite; Vachellia farnesiana; arthropoda; D-Vac; honey mesquite; huisache; grubbing; Prosopis glandulosa; stacking; sweep net